Resistin induces breast cancer cells epithelial to mesenchymal transition (EMT) and stemness through both adenylyl cyclase-associated protein 1 (CAP1)-dependent and CAP1-independent mechanisms. (August 2019) - Avtanski, Dimiter; Garcia, Anabel; Caraballo, Beatriz; Thangeswaran, Priyanthan; Marin, Sela; Bianco, Julianna; Lavi, Aaron; Poretsky, Leonid
Highlights: Reistin increases cellular motility of breast cancer and non-carcinogenic cells. Resistin induces EMT and aquisition of CSC properties in breast cancer cells. The effects of resistin on EMT and cancer stemness are partially dependent on CAP1. Abstract: Breast cancer incidence and metastasis in postmenopausal women are known to associate with obesity, but the molecular mechanisms behind this association are largely unknown. We investigated the effect of adipokine resistin on epithelial to mesenchymal transition (EMT) and stemness in breast cancer cells in vitro . Previous reports demonstrated that the inflammatory actions of resistin are mediated by the adenylyl cyclase-associated protein 1 (CAP1), which serves as its receptor. As a model for our study, we used MCF-7 and MDA-MB-231 breast cancer and MCF-10A breast epithelial cells. We showed that in MCF-7 cells resistin increases the migration of MCF-7 and MDA-MB-231 cells and induces the formation of cellular protrusions through reorganization of F-actin filaments. Resistin upregulated the expression of mesenchymal markers involved in EMT (SNAIL, SLUG, ZEB1, TWIST1, fibronectin, and vimentin), and downregulated those of epithelial markers (E-cadherin and claudin-1). Resistin also potentiated the nuclear translocation of SNAIL protein, indicating initiation of EMT reprogramming. We further induced EMT in non-carcinogenic breast epithelial MCF-10A cells demonstrating that the effects of resistin on EMT were not breast cancer cell specific. In order to assess whether resistin-induced EMT depends on CAP1, we used siRNA approach to silence CAP1 gene in MCF-7 cells. Results demonstrated that when CAP1 was silenced, the induction of SNAIL, ZEB1 and vimentin expression by resistin as well as SNAIL and ZEB1 nuclear translocation, were abolished. Additionally, CAP1 silencing resulted in a suppression of MCF-7 cells migration. We performed quantitative PCR array profiling the expression of 84 genes related to cancer stem cells (CSC), pluripotency and metastasis and selected a set of genes (ALDH1A1, ITGA4, LIN28B, SMO, KLF17, PTPRC, PROM1, SIRT1, and PECAM1) that were modulated by resistin. Further experiments demonstrated that the effect of resistin on the expression of some of these genes (PROM1, PTPRC, KLF17, SIRT1, and PECAM1) was also dependent on CAP1. Our results demonstrate that resistin promotes the metastatic potential of breast cancer cells by inducing EMT and stemness and some of these effects are mediated by CAP1.